Clinico-Epidemiological Study Of Adult Acute Poisoning At Tertiary Care Centrein Hadoti Region: A Cross Sectional Study (Indian Journal of Forensic Medicine & Toxicology, 2024)
Objective: To study Clinico-epidemiological parameters of adult acute poisoning at tertiary care centre in Hadoti region of Rajasthan.Methodology: A prospective cross sectional was conducted on 50 patients, presenting to the Government medical college and associated group of hospitals of Kota, Rajasthan. The data about demography and laboratory parameters were collected after admission of the patient and analyzed.Results: The mean age of patients was 28.4(13.0-58.0) years. The proportion of male was 62%. Most common mode of poisoning was ingestion(98%). suicidal circumstance was in 45 (90%) (Male:Female=2:1) and accidental in 5 (10%) patients (Male:Female=1:4). Most of the suicidal  poisoning cases (34%) from the age group 20 to 29 years. Insecticidal poisoning was the most common poisoning. In drug poisoning most common  from sedative group or benzodiazepine group, in corrosive poisoning most common was Phenyl. The most common symptom was Vomiting (90%). 48 patients were successfully discharged from ward or ICU and 2 were expired from ICU.Conclusion: Study has provided a comprehensive overview of poisoning in Rajasthan, focusing on hospital data. The findings indicate that male gender and longer delays in seeking treatment at primary care facilities are associated with lower survival rates. The study highlights the need for increased public awareness about the importance of promptly transferring poisoning cases to hospitals, calling for attention from planners and policy-makers.
Keywords: Adult poisoning; Hadoti region